CNA-loaded PLGA nanoparticles improve humoral response againstS. aureus-mediated infections in a mouse model: subcutaneous vs. nasal administration strategy. (16th November 2016) - Genta, Ida; Colonna, Claudia; Conti, Bice; Caliceti, Paolo; Salmaso, Stefano; Speziale, Pietro; Pietrocola, Giampiero; Chiesa, Enrica; Modena, Tiziana; Dorati, Rossella
Abstract: The aim of this work was the assessment of the " in vivo " immune response of a poly(lactide-co-glycolide)-based nanoparticulate adjuvant for a sub-unit vaccine, namely, a purified recombinant collagen-binding bacterial adhesion fragment (CNA19), against Staphylococcus aureus -mediated infections. " In vivo " immunogenicity studies were performed on mice: immunisation protocols encompassed subcutaneous and intranasal administration of CNA19 formulated as nanoparticles (NPs) and furthermore, CNA19-loaded NPs formulated in a set-up thermosetting chitosan-β-glycerolphosphate (chitosan-β-GP) solution for intranasal route in order to extend antigen exposure to nasal mucosa. CNA19 loaded NPs (mean size of about 195 nm, 9.04 ± 0.37μg/mg as CNA19 loading capacity) confirmed as suitable vaccine for subcutaneous administration with a more pronounced adjuvant effect (about 3-fold higher) with respect to aluminium, recognised as "reference" adjuvant. CNA19 loaded NPs formulated in an optimised thermogelling chitosan-β-GP solution showed promising results for eliciting an effective humoral response and a good chance as intranasal boosting dose.